Checklist of earthworm species (Oligochaeta) of the North Eastern Region of India - Tiwari, Nalini; Paliwal, R.; Rashid, Azhar; Yadav, Shweta (Zootaxa, 2020)
A checklist of earthworm species hitherto recorded from North Eastern Region (NER) of India is presented. In total, 128 species/subspecies belonging to 26 genera spread over 9 families are listed. Of these, 72 species are recognized as endemics, 18 as near endemics, 5 as native peregrines and 32 as exotics. The checklist includes literature citation to the original description, type locality, important synonyms and the state-wise distributional records for each species/subspecies.